Dietary Alpha-Ketoglutarate Supplementation Improves Bone Growth, Phosphorus Digestion, and Growth Performance in Piglets - Junquan Tian; Fan Yang; Xuetai Bao; Qian Jiang; Yuying Li; Kang Yao; Yulong Yin (Animals, 2023)
Phosphorus (P) pollution from modern swine production is a major environmental problem. Dietary interventions to promote bone growth can improve the utilization of dietary P, and thereby reduce its emission. Recent in vitro studies have shown that alpha-ketoglutarate (AKG) exerts a pro-osteogenic effect on osteoblast cells. This study aimed to evaluate the effects of AKG supplementation on bone growth, P and Ca digestion, and the gut microbial profile in piglets. Thirty-two piglets were randomly assigned into two dietary groups. The piglets were fed a basic diet containing 10 g/kg AKG or 10 g/kg maize starch (control) for 28 days. On days 21–28, titanium dioxide was used as an indicator to determine the apparent digestibility of P. AKG supplementation improved the bone mineral density, length, weight, and geometrical and strength properties of the femur and tibia. Furthermore, AKG supplementation increased apparent ileal and total tract digestibility of P. Colonic microbiota analysis results showed that AKG supplementation increased α-diversity and beneficial bacteria, including Lactobacillus and Clostridium butyricum, and decreased nitrogen fixation and chemoheterotrophy. Together, AKG supplementation improves bone growth, the utilization of dietary P, and the colonic microbial profile, which may provide a nutritional strategy for diminishing P pollution originating from the pig industry.